Design of Water Balance Water System in Plant Based Sensor Moisture and Microcontroller Arduino Uno - Muhammad Bayu Wibawa (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
The balance in the plant maintenance is one of the main things that must be taken into account. The balance in maintenance is how to keep the plants adequate nutritional well water, fertilizer and other maintenance fields. Water is a major component to be considered. Without water, the plants will wither and die. Keeping the water in the soil sufficient means one should always monitor the soil moisture from drying or no excess water. To maintain and monitor the soil moisture was always a farmer must always maintain the plant to produce optimal plant. The level of mobility is also greater if farmers have to control the plant, especially relating to water balance in plants. Then needed a tool to maintain the water balance in plants by looking at soil moisture conditions as if the dry soil moisture and water will automatically watering plants, and vice versa if the water moisture in wet conditions then no wateringKeywords : Prototype Automatic light , Microcontroller Arduino Uno , Infra Red Sensor